2006
DOI: 10.1002/aic.10933
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic pH measurement for high temperatures, pressures and ionic strength

Abstract: Accurate measurement of pH is important in several diverse fields, such as process control, reaction equilibrium and kinetics, environmental research to monitor seawater chemistry and natural water quality, biomedical research and in oilfields. The International Union of Pure and Applied Chemistry (IUPAC) has issued guidelines for the standard potentiometric technique for pH measurements. These methods and calibrating standards are, however, recommended only for 278 -323°K, 0.101325 MPa and ionic strengths bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
0
18
2
Order By: Relevance
“…Here a shift in the ee of 2-HPP towards higher excess of (S)-2-HPP was observed by decreasing pH from pH 7.5 to pH 6.5 (Berheide et al, 2010). However, it is reported in literature that an increase in pressure leads to a decrease in pH (Raghuraman et al, 2006). Thus our results revealed that the pressure effect on the enantioselectivity of BFD is a separate and contrary effect compared to the pH effect.…”
Section: Influence Of Ph On Bfd-catalyzed Enantioselective Synthesis contrasting
confidence: 76%
See 1 more Smart Citation
“…Here a shift in the ee of 2-HPP towards higher excess of (S)-2-HPP was observed by decreasing pH from pH 7.5 to pH 6.5 (Berheide et al, 2010). However, it is reported in literature that an increase in pressure leads to a decrease in pH (Raghuraman et al, 2006). Thus our results revealed that the pressure effect on the enantioselectivity of BFD is a separate and contrary effect compared to the pH effect.…”
Section: Influence Of Ph On Bfd-catalyzed Enantioselective Synthesis contrasting
confidence: 76%
“…We showed that the tendency towards higher (R)-selectivities observed at high pressures could be enhanced when the reactions were run under alkaline conditions. In literature pressure induced pH shifts were analyzed especially for aqueous buffer systems and acid/base equilibria (Neumann et al, 1973;Morild, 1977;Marshall and Franck, 1981;Cavaille and Combes, 1996;Raghuraman et al, 2006). Raghuraman et al (2006) developed a calibration procedure for pH sensitive dyes using chemical equilibrium models.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the three deprotonation equilibria of phosphoric acid in water the pH of phosphate buffers significantly decreases by increasing pressure (Raghuraman et al, 2006). To exclude a pH-related effect on the enantioselectivity of BFD caused by a pressureinduced pH-shift, the formation of 2-HPP by BFD was investigated at different pH-values and benzaldehyde concentrations.…”
Section: Reversibility Of the Pressure-induced Changes In Enantioselementioning
confidence: 99%
“…Consequently, DFA pH measurements are generally much more accurate than normal laboratory pH measurements of oilfield waters. [26,27] Figure 18 shows the composition of gases from different compartments in a single field. [25] The CO2 content is seen to vary enormously in these samples.…”
Section: Downhole Fluid Analysis (Dfa)mentioning
confidence: 99%
“…[24] Of course, CO2 can affect corresponding water pH, and this too can be measured downhole. [26] Indeed, aqueous samples are normally cooled and flashed before laboratory pH measurements, which allows carbonate solids to precipitate and CO2 gas to evolve. Consequently, DFA pH measurements are generally much more accurate than normal laboratory pH measurements of oilfield waters.…”
Section: Downhole Fluid Analysis (Dfa)mentioning
confidence: 99%